APLIKASI ALGORITMA DECISION TREE C4.5 SEBAGAI MODEL PENDUKUNG KEPUTUSAN SELEKSI ANGGOTA RESIMEN MAHASISWA UNIVERSITAS UDAYANA - WIBISONO, ALEXANDER HIRO; KENCANA, I PUTU EKA NILA; SUMARJAYA, I WAYAN (E-Jurnal Matematika, 2022)
The Reserve Officer Training Corps (ROTC) of the 901 st Mayurajana Battalion. The 2000 Agreement caused the ROTC to be excluded from the Indonesian Military command structure, causing the ROTC in each campus to have a diverse standard of members due to the recruitment process which are done by students. C4.5 algorithm from chefboost was used to find the accuracy as well as assist the construction of an ideal C4.5 algorithm. The result shows the C4.5 algorithm by chefboost to have a 79.16% accuracy with the tendency to underestimate the data. During the modeling of the algorithm it is discovered that the source of the algorithm’s tendency to underestimate the data appears to be affected by the recruits administration and medical history.